(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Type 1 diabetes mellitus (T1DM) is an endocrine disease associated with hereditary and autoimmune processes, which is common in young children and adolescents. Its early detection and prognosis are important. Dermatoglyphics is a method for studying the papillary lines of the skin of the fingers and palms, which contains information related to genetic and embryonic development. In this study, dermatoglyphic features in children with T1DM were studied, their susceptibility to the disease and their significance in diagnosis were assessed. The results showed that the changes in papillary lines, the relatively low number of spots and the increased number of whorls in children with type 1 diabetes were associated with their genetic pathology. The results of the study will help to improve the possibilities of forensic examination and early detection of the disease using dermatoglyphic analysis.